2018
DOI: 10.5664/jcsm.7098
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea is an Independent Risk Factor for Hospital Readmission

Abstract: This study found OSA to be an independent risk factor for readmission within 30 days of discharge. PAP therapy appears to be underutilized in patients with known OSA. Additional studies are needed to define the relationship between OSA, PAP adherence, and hospital readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…The study did, however, find an association between calcification and OSA, when calcification was measured by segment involvement score and segment stenosis score. A US study of general medicine patients reported OSA as a risk factor for readmission (11.4% vs. 7.6%, p < 0.01) [31]. Thus, OSA may be an important novel modifiable risk factor for cardiovascular readmissions.…”
Section: Sleep and Readmissionsmentioning
confidence: 99%
“…The study did, however, find an association between calcification and OSA, when calcification was measured by segment involvement score and segment stenosis score. A US study of general medicine patients reported OSA as a risk factor for readmission (11.4% vs. 7.6%, p < 0.01) [31]. Thus, OSA may be an important novel modifiable risk factor for cardiovascular readmissions.…”
Section: Sleep and Readmissionsmentioning
confidence: 99%
“…[7][8][9] Patients with OSA are known to have difficulties with intubation, more frequent admissions to the intensive care unit (ICU), more postoperative complications, longer duration of hospital stay, and increased hospital readmission. 2,3,[10][11][12][13][14] Undiagnosed and/or untreated sleep apnea can lead to adverse events and morbidity in hospitalized patients receiving care for other illnesses or injuries. Hospitals often deploy a rapid response or medical emergency team (MET) when patients show signs of deterioration in order to rapidly identify and intervene to prevent fatal decline in patient status.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a common condition in subjects from both sex and all ages 1 , 2 , and it is associated with higher morbidity and mortality 3 , 4 . In Brazilian population, the presence of severe OSA (apnea-hypopnea index - AHI≥15) was predictor of hospitalizations and/or demand for emergency services 5 . Recently, Scalzitti et al 5 analyzed more than 22,000 patients to identify factors that contribute to hospital readmission within 30 days of discharge.…”
mentioning
confidence: 99%
“…In Brazilian population, the presence of severe OSA (apnea-hypopnea index - AHI≥15) was predictor of hospitalizations and/or demand for emergency services 5 . Recently, Scalzitti et al 5 analyzed more than 22,000 patients to identify factors that contribute to hospital readmission within 30 days of discharge. Authors found that OSA was an independent risk factor for readmission 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation